Теоретично про конструктив обмоток електричних двигунів з можливістю покращення їх характеристик - Юрченко, Олександр Юрійович; Барсукова, Ганна Володимирівна; Мороз, Костянтин; Новіков, Микита; Щебетенко, Максим; Yurchenko, Oleksandr; Barsukova, Hanna; Moroz, Kostiantyn; Novikov, Mykyta; Shchebetenko, Maksym (Запоріжжя : Видавничій дім "Гельветика", 2025)
UA: Покращення характеристик електричних двигунів є можливим шляхом зміни конструкції їх обмоток. Збільшення рівня використання електричних двигунів у різних галузях на різних режимах роботи вимагає підходу, спрямованого на раціональне використання ресурсів. У роботі на прикладі конкретно обраного електричного двигуна представлено аналіз можливості підвищення його потужності шляхом зменшення довжини петлі в лобовій частині обмотки електричного двигуна. Як наслідок, зменшення довжини петлі в лобовій частині з 70 мм до 20 мм для конкретного електричного двигуна призводить до зменшення довжини витка обмотки в 1,8 раза, що дає змогу зменшити опір котушок, що встановлені в пазах електричного двигуна. Зменшення опору дає змогу збільшити силу струму, а отже, і потужності цього електродвигуна, а також раціонального використання габаритів двигуна та проводу у витках котушок його обмоток. /// EN: Improving the characteristics of electric motors is possible by changing the design of their windings. Increasing the level of use of electric motors in different industries in different operating modes requires an approach aimed at rational use of resources. In this paper, using the example of a specifically selected electric motor, an analysis of the possibility of increasing its power by reducing the length of the loop in the frontal part of the winding of the electric motor is presented. As a result, reducing the length of the loop in the frontal part from 70 mm to 20 mm for a specific electric motor leads to a reduction in the length of the winding turn by 1.8 times, which thereby makes it possible to reduce the resistance of the coils installed in the slots of the electric motor. Reducing the resistance makes it possible to increase the current strength, and, consequently, the power of this electric motor, as well as rational use of the dimensions of the motor and the wire in the turns of the coils of its windings. Making changes to the design of an electric motor is possible due to the length of the winding turn that is inserted into the grooves. By performing an analysis of the design characteristics of the windings of an electric motor on the example of a specific 5.5 kW motor with one pair of poles, this work considers the possibility of rational use of the dimensions of the electric motor, as well as the power given at its output. It has been established that one loop length (of the frontal part of the winding of a specifically selected electric motor) is greater than the length of the active steel. As a result, rational use of the dimensions and resource of the electric motor can be aimed at reducing the loop in the winding coil. By reducing the loop (two at once) in each of the turns of the winding coil, it is possible to reduce the resistance of the wire. Further research on the topic would be advisable to focus on determining the temperature indicators of an electric motor, which will change with increasing current strength, and therefore power.
Theoretically about the design of electric motor windings with the possibility of improving their characteristics
Keywords: електричний двигун; котушка; обмотка; активна сталь; провід; статор; ротор; пари полюсів; потужність; сила струму; опір; напруга; питомий опір; довжина провідника; площа поперечного перерізу; габаритні розміри; раціональне використання; підвищення ефективності; electric motor; coil; winding; active steel; wire; stator; rotor; pole pairs; power; current; resistance; voltage; resistivity; conductor length; cross-sectional area; overall dimensions; rational use; efficiency improvement